The relationship between maternal methadone dose at delivery and neonatal outcome: Methodological and design considerations - Jones, Hendrée E. (2013)
Compared to untreated opioid dependence, methadone maintenance treatment of opioid-dependent pregnant women has been found to be associated with better maternal and neonatal outcomes. Secondary analysis of data from 73 maternal and neonatal participants in the MOTHER study (H. E. Jones et al., New England Journal of Medicine, 2010) found no relationship between maternal methadone dose at delivery and any of 9 neonatal outcomes – peak neonatal abstinence syndrome (NAS) score, total amount of morphine needed to treat NAS, duration of neonatal hospital stay, duration of treatment for NAS, estimated gestational age at delivery, Apgar score at 5 minutes, and neonatal head circumference, length, and weight at birth. These results are consistent with a recent systematic review and meta-analysis (B. J. Cleary et al., Addiction, 2010) and extend findings to outcomes other than NAS. Methodological and design issues that might have adversely impacted the ability of researchers to establish the existence or non-existence of these relationships are considered.